2011
DOI: 10.2478/s11536-011-0119-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential characteristics of anxiety syndromes in clinical adolescents

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…So far, research on the relationship between JTCI and depression among adolescents is sparse. A few studies have reported associations between JTCI and psychopathology in adolescents [ 34 38 ]. Schmeck and colleagues [ 34 ] reported a negative correlation between several forms of psychopathology, including anxiety and depression and SD.…”
Section: Introductionmentioning
confidence: 99%
“…So far, research on the relationship between JTCI and depression among adolescents is sparse. A few studies have reported associations between JTCI and psychopathology in adolescents [ 34 38 ]. Schmeck and colleagues [ 34 ] reported a negative correlation between several forms of psychopathology, including anxiety and depression and SD.…”
Section: Introductionmentioning
confidence: 99%